Metal selenide semiconductor thin films: A review - Ho, Soon Min (2016)
Recent research has emphasized on the preparation of metal chalcogenide thin films such as metal sulfide, metal selenide and metal telluride by using various deposition techniques. Because of these thin films possess very useful physical properties and could be found in many technical applications. In this review paper, study of the properties of metal selenide thin films will be reported.